Recent developments in the field of cachexia, sarcopenia, and muscle wasting: highlights from the 12th Cachexia Conference. Issue 1 (12th February 2020) - Ebner, Nicole; Anker, Stefan D.; von Haehling, Stephan
Abstract: This article highlights preclinical and clinical studies in the field of wasting disorders that were presented at the 12th Cachexia Conference held in Berlin, Germany, in December 2019. Herein, we summarize the biological and clinical significance of different strategies including antibodies that target Fn14, Spsb 1, SAA1 treatment, ZIP14, a MuRF1 inhibitor, and new diagnostic tools like T‐cell communication targets and cut‐offs for the detection of skeletal muscle wasting. Of particular interest were the transplantation of mesenchymal stromal cells and muscle stem cell communication. Importantly, one presentation discussed the effect of metal ion transporter ZIP14 loss that reduces cancer‐induced cachexia. The potential of anti‐ZIP14 antibodies and zinc chelation as anti‐cachexia therapy may require testing in patients with cancer cachexia. Large clinical studies were presented such as RePOWER (observational study of patients with primary mitochondrial myopathy), MMPOWER (treatment with elamipretide in patients with primary mitochondrial myopathy), and ACT‐ONE as well as new mouse models like the KPP mouse. Promising treatments include rapamycin analogue treatment, anamorelin, elanapril, glucocorticoids, SAA1, antibodies that target Fn14, and a MuRF1 inhibitor. Clinical studies investigated novel approaches, including the role of exercise. It remains a fact, however, that effective treatments for cachexia and wasting disorders are urgently needed in order to improve patients' quality of life and their survival.